A retrospective study of the Hall technique for the treatment of carious primary teeth in Sydney, Australia. Issue 5 (8th April 2021) - Sapountzis, Fani; Mahony, Tanya; Villarosa, Amy R.; George, Ajesh; Yaacoub, Albert
Abstract: Objectives: The aim of this retrospective study was to evaluate the outcome of preformed metallic crowns (PMC) utilizing the HT in carious primary molars for children treated within public dental clinics across the Sydney region. Materials and Methods: A retrospective cohort study was designed, whereby two investigators evaluated 113 primary molars treated with HT PMCs involving 71 participants (aged between 5 and 11 years) after a minimum of 6 months post treatment. The mean time elapsed between crown placement (treatment) and the review was 1.42 years (17 months). The outcome of the HT was assessed by clinical and radiographic criteria. Results: One hundred thirteen HT PMCs were reviewed from 71 participants. The overall success rate of PMCs placed utilizing the HT was 99%, with only one case presenting with confirmed failure. Conclusions: HT PMCs have an overall high success rate as a treatment option in carious primary molars.